Phospho-ΔNp63α-dependent regulation of autophagic signaling through transcription and micro-RNA modulation - Huang, Yiping (Landes Bioscience, 2012)
Cisplatin was shown to induce the ataxia telangiectasia mutated (ATM)-dependent phosphorylation of tumor protein p63 isoform, (ΔNp63α), leading to a transcriptional regulation of specific genes implicated in the control of cell death of squamous cell carcinoma (SCC) cells. We previously observed that the cisplatin-induced phosphorylated (p)-ΔNp63α transcriptionally regulates the expression of specific microRNAs (miRNAs) in SCC cells. We found here that cisplatin exposure of SCC cells led to modulation of the members of the autophagic pathway, such as Atg1/Ulk1, Atg3, Atg4A, Atg5, Atg6/Becn1, Atg7, Atg9A and Atg10, by a direct p-ΔNp63α-dependent transcriptional regulation. We further found that specific miRNAs (miR-181a, miR-519a, miR-374a and miR-630), which are critical downstream targets of the p-ΔNp63α, modulated the protein levels of ATG5, ATG6/BECN1, ATG10, ATG12, ATG16L1 and UVRAG, adding another level of expression control for autophagic pathways in SCC cells upon cisplatin exposure. Our data support the notion that the cisplatin-induced p-ΔNp63α could regulate key pathways implicated in response of cancer cells to chemotherapeutics.